Sagot :
Answer:
N = - 22
Step-by-step explanation:
Step 1: Write the algebraic expression.
3(x-5) = 5x-93(x−5)=5x−9
wherein:
xx is the number
Understanding algebraic expression
"5 less than a number" is written as "x-5x−5 "
"result" means "is equal to"
"9 less than 5 times the number" is written as "5x-95x−9 "
"7 less than 5 times the number" is written as "5x-75x−7 "
Step 2: Solve for the value of xx using distributive property of multiplication
3(x-5) = 5x-93(x−5)=5x−9
3x-15 = 5x-93x−15=5x−9
-2x = 6−2x=6
x = -3x=−3
Step 3: Find the "7 less than 5 times the number" by substituting the value of xx
N=5x-7N=5x−7
where NN is the desired output
N=5(-3)-7N=5(−3)−7
N=-15-7N=−15−7
N=-22N=−22
Topic related to question: Algebraic expression.
Step-by-step explanation:
Hope its helpp:))